Pelatihan Teknik Copywriting untuk Promosi Wisata Melalui Media Sosial - Husen, Tamitha Intassar; Hadi, Fajri; Hidayat, Muhammad Rahmat; yusnaidi, yusnaidi; Fatmayanti, Fatmayanti (Universitas Teuku Umar, 2023)
In the dynamic realm of modern tourism promotion, the influence of social media cannot be ignored. As the digital landscape continues to evolve, the art of copywriting is emerging as an indispensable tool for capturing audiences and driving target market engagement. This article discusses the implementation of copywriting training in the context of promoting tourist destinations on social media platforms. By exploring the interplay between persuasive language, storytelling, and the immersive nature of social media, this article highlights how effective copywriting techniques can transform ordinary travel narratives into engaging and irresistible tales. Through comprehensive analysis of successful campaigns, it uncovers strategies for creating compelling content that resonates with diverse audiences, elicits emotional connection, and ultimately fosters a desire to explore the causes on display. The implementation of this copywriting training has added insight to harness the power of words to arouse the desire to visit and inspire tourists to start a pleasant tour.